Depression in Kidney Transplant Recipients - Maytinee Srifuengfung (2018)
Copyright © 2017 Wolters Kluwer Health, Inc. All rights reserved. This study examined the prevalence, risk factors, and disability associated with depression. We conducted a cross-sectional, observational study in 217 consecutive kidney transplant (KT) recipients routinely followed-up at a Kidney Transplantation Clinic in Northern Thailand. Participants were assessed using the Charlson Comorbidity Index (CCI), the nine-item Patient Health Questionnaire (PHQ-9), and the 12-item self-report of World Health Organization Disability Assessment Scale, Version 2.0 (WHODAS). Twenty-eight (12.9%) patients had depression (PHQ-9 score, ≥10). A binary logistic regression analysis found that the CCI score was significantly higher in KT recipients with depression ( = 0.54, p < 0.01). After the adjustment of education and glomerular filter rates, an ordinal logistic regression analysis revealed that the PHQ-9 scores were positively correlated with the WHODAS scores (β = 0.39, p < 0.01). In KT recipients, physical comorbidity is associated with depression, and depression is correlated with functional disability.